Advanced Nano-Carriers for Anti-Tumor Drug Loading - Xiang, Jia; Zhao, Rui; Wang, Bo; Sun, Xinran; Guo, Xu; Tan, Songwen; Liu, Wenjie (Frontiers in Oncology, 2021)
Chemotherapy is one of the important means of tumor therapy. However, most of the anti-tumor drugs that currently used in clinic are hydrophobic non-specific drugs, which seriously affect the efficacy of drugs. With the development of nanotechnology, drug efficacy can be improved by selecting appropriate biodegradable nanocarriers for achieving the controlled release, targeting and higher bioavailability of drugs. This paper reviewed the research progress of anti-tumor drug nanoparticle carriers, which mainly summarized the materials used for anti-tumor drug nanoparticle carriers and their effects in antitumor drugs, as well as the targeted drug delivery methods of antitumor drugs based on nanoarriers